2023
DOI: 10.1007/s00423-023-02905-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrent disease in small papillary thyroid cancers – a Swedish register-based study

Abstract: Aims To study the correlation between clinicopathological risk factors and the risk for intervention-requiring cancer recurrence in patients with small papillary thyroid cancers (sPTCs). Materials and methods Records for 397 patients with sPTC (T1 ≤ 20mm) were obtained from the Scandinavian Quality Register for Thyroid, Parathyroid and Adrenal Surgery (SQRTPA) between 2010 and 2016. Follow-up time was at least 5 years. Data regarding intervention-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…LLNM is associated with a poor prognosis in patients ( 46 ). Nevertheless, the current indication for performing cervical lateral lymph node dissection in PTC cases remain subject to debate.…”
Section: Discussionmentioning
confidence: 99%
“…LLNM is associated with a poor prognosis in patients ( 46 ). Nevertheless, the current indication for performing cervical lateral lymph node dissection in PTC cases remain subject to debate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found associations among the number and maximum diameter of lymph node metastases and the malignancy of the primary tumor, as well as with postoperative local recurrence and survival prognosis for patients with PTC (10). Patients with small-volume or no lymph node metastasis demonstrate similar postoperative recurrence rates (11), which is significantly better than patients with meddle or large-volume lymph node metastasis (>5 lymph nodes and/or a metastatic focus diameter ≥ 0.2 cm) (12,13). Therefore, PTC patients with small-volume lymph node metastasis may be defined as low-risk preoperatively, allowing for the selection of more suitable treatment approaches.…”
Section: Discussionmentioning
confidence: 99%